Jogos imaginários e movimentos das posições-sujeito: unidade/dispersão no discurso de formação docente - Carneiro, Ana Paula Sarmento (2010)
In this work, we goal is to analyze continuous formation discourse from Portuguese teachers in academic context, emphasizing the relation that the subject keep with knowledge/power, with him/herself, with the other and gender writing skills. The data produced by this research are derived from a teachers‟ formation course, which were offered by a graduation program from a federal university of Paraíba (Brazil). Such course was ministered by Language professors from this university. Based on theoretical concepts of French Discourse Analysis, we intended to verify subject position movements about knowledge/power, with the aim of reflexive journals which were written by the ministrant professors and by teachers/students. Such journals point to different discursive orders, causing a unity effect, when it comes to release a discursive memory of knowledge accomplishment and institutionalization and, at the same time, another discursive order which questioned ways of systematization, progression and classification of knowledge, inclusively, of institutionalization and authority of professor‟s knowledge. When it comes to the relation of professors with themselves and with the other, we have noticed and image and identity movement game which somehow reflected the discursive confrontation over the teaching object among the teachers who were participating of the formation course. We have also evidenced through the reflexive journals that dislocations in the self image took place with the professors, especially because of writing place legitimation which the teachers attributed to the professors, as well as the rescue of an authority memory and legitimation of professor‟s qualified/master place in relation to the teachers. Such subject places legitimation (professors and teachers) have also provoked dislocations when it comes to author-effect in the writing of the gender opinion article.